2021
DOI: 10.1177/23312165211023709
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Three Auditory Profiles on Aided Speech Perception in Different Noise Scenarios

Abstract: Hearing aid (HA) users differ greatly in their speech-in-noise (SIN) outcomes. This could be because the degree to which current HA fittings can address individual listening needs differs across users and listening situations. In two earlier studies, an auditory test battery and a data-driven method were developed for classifying HA candidates into four distinct auditory profiles differing in audiometric hearing loss and suprathreshold hearing abilities. This study explored aided SIN outcome for three of these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 58 publications
1
11
0
Order By: Relevance
“…However, before the clinical biomarkers can be established, patient subpopulations with a likely different response to different treatments must be identified. This has been explored in Wu et al ( 2020 , 2021 ) and Sanchez Lopez et al ( 2021 ). A profile-based hearing-aid fitting process has also been implemented in a large field study within the BEAR project.…”
Section: Discussionmentioning
confidence: 99%
“…However, before the clinical biomarkers can be established, patient subpopulations with a likely different response to different treatments must be identified. This has been explored in Wu et al ( 2020 , 2021 ) and Sanchez Lopez et al ( 2021 ). A profile-based hearing-aid fitting process has also been implemented in a large field study within the BEAR project.…”
Section: Discussionmentioning
confidence: 99%
“…In earlier work by the authors, large inter-individual differences were observed among profile-C listeners, that is, HA users with profound hearing deficits (Wu et al, 2021, 2020). In the current study, it was hypothesized that cognitive factors would be able to account for at least some of these differences.…”
Section: Discussionmentioning
confidence: 86%
“…For those 28 participants tested by Wu et al (2021), their aided outcome data obtained with the same HA (Oticon Opn S1) were reused in the current study. Since the current study followed up on the study of Wu et al (2021), the same fitting procedure was applied here. The individual gains from the proprietary fittings were documented through real ear measurements (REM) in Wu et al (2021).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Spearman’s correlation coefficient showed a moderate correlation between left and right ears ( r S = 0.46, p = 0.005). Within-subject differences between the tested ears exceeded 1.3 dB in 20 participants and thus fell outside the 95% test-retest CI for this task, as calculated based on a within-subject SD of 0.7 dB SNR estimated using data from Nielsen and Dau (2011) and Wu et al (2021). Thus, the majority of the participants showed a small but significant difference in HINT performance across ears.…”
Section: Resultsmentioning
confidence: 92%